Refining Zooplankton Diet Composition Studies Over Short and Long Time Scales by Combining 18S Metabarcoding With Fatty Acid Analyses - Pauli, Nora-Charlotte; Metfies, Katja; Neuhaus, Stefan; Graeve, Martin; Cleary, Alison C.; Iversen, Morten H.; Meyer, Bettina (Molecular Ecology Resources, 2025)
ABSTRACT Understanding diet composition is essential for unravelling trophic interactions in aquatic ecosystems. DNA metabarcoding, utilising various variable regions of the 18S rRNA gene, is increasingly employed to investigate zooplankton diet composition. However, accurate results depend on rapid inactivation of digestive enzymes and DNA nucleases through proper sample processing and preservation. In this study, we compare the prey communities of Antarctic krill retrieved from the 18S variable regions V4 and V7 and assess how different processing treatments affect the detected prey composition of both krill and salps. Our findings highlight the critical importance of prompt sample processing for species with highly efficient digestive enzymes, such as krill, to preserve rapidly digested prey, including gelatinous plankton. Comparative analyses of the V4 and V7 regions revealed significantly different prey communities within the same krill samples, indicating that these regions may not be suitable for direct comparisons within or across studies. To complement molecular approaches, we also analyse fatty acids (FA) as trophic markers which provide insights into dietary habits over both short and long time scales. By comparing FA signals from stomach and tissue samples of the same krill and salp individuals, we identified significant differences in trophic markers representing different plankton groups. These findings emphasise the necessity of separating digestive tract from tissue to distinguish between short- and long-term diet signals. Furthermore, integrating FA analysis with metabarcoding offers valuable insights into zooplankton digestion efficiency across taxonomic levels. This combined approach enhances our understanding of zooplankton feeding ecology and trophic interactions in marine ecosystems.
Publisher: John Wiley & Sons, Ltd Article Number: e70030
Keywords: Sørishavet; Weddellhavet; genetikk; krill; marin biologi; marine økosystemer; zooplankton

Basal Melt Rate Variability and Tidal Current Vertical Structure From Observations Beneath Ronne Ice Shelf, Antarctica - Anselin, J.; Nicholls, K. W.; Holland, P. R.; Taylor, J. R.; Østerhus, S.; Makinson, K. (Journal of Geophysical Research: Oceans, 2025)
This study examines the interplay between water column structure, tidal currents, and basal melting at a site beneath Ronne Ice Shelf, using a 3-year data set of oceanographic measurements, and a collocated year-long time series of radar-derived melt rate estimates. Currents at the site are characterized by mixed semidiurnal tides with strong spring-neap variability, superimposed on a nontidal flow. The product of current speed and thermal driving, both measured approximately 19 m from the ice base, explains 88% of the melt rate variability. Although current speed is the dominant driver of this variability, thermal driving also contributes non-negligibly on spring-neap and longer timescales. The semidiurnal tidal ellipses feature marked vertical variations, transitioning from nearly rectilinear in the mid-water column to more circular and clockwise (CW)-rotating near the ice. This depth-dependence of the semidiurnal tide is attributed to the differential influence of boundary friction on the CW and anticlockwise (ACW) rotary components near the critical latitude (where the tidal frequency equals the Coriolis frequency). A theoretical model, which assumes depth-independent eddy viscosity, successfully reproduces the observed 3-year mean vertical structure of the tidal ellipses. Considering the total tidal current rather than individual constituents, ice base friction damps both the time-mean flow speed and the tidal fluctuations, with attenuation varying over the spring-neap cycle, peaking during spring tides. The observed latitude- and time-dependent effects of ice base friction on the barotropic tide are not captured in parameterizations that estimate tide-induced friction velocity by scaling the time-averaged barotropic tidal speed with a constant drag coefficient.
Publisher: John Wiley & Sons, Ltd Article number: e2025JC022524
Keywords: Antarktis; Sørishavet; Weddellhavet; glasiologi; hydrografi; isshelf; oseanografi

A new dynamic distribution model for Antarctic krill reveals interactions with their environment, predators, and the commercial fishery in the south Scotia Sea region - Freer, Jennifer J.; Warwick-Evans, Victoria; Skaret, Georg; Krafft, Bjørn A.; Fielding, Sophie; Trathan, Philip N. (Limnology and Oceanography, 2025)
The management strategy for the Antarctic krill (Euphausia superba) fishery is being revised. A key aim is to spatially and temporally allocate catches in a manner that minimizes impacts to both the krill stock and dependent predators. This process requires spatial information on the distribution and abundance of krill, yet gaps exist for an important fishing area surrounding the South Orkney Islands in the south Scotia Sea. To fill this need, we create a dynamic distribution model for krill in this region. We used data from a spatially and temporally consistent acoustic survey (2011-2020) and year-specific environmental covariates within a two-part hurdle model. The model successfully captured observed spatial and temporal patterns in krill density. The covariates found to be most important included distance from shelf break, distance from summer sea ice extent, and salinity. The northern and eastern shelf edges of the South Orkney Islands were areas of consistently high krill density and displayed strong spatial overlap between intense fishing activity and foraging chinstrap penguins. High mean krill density was also linked to oceanographic features located within the Weddell Sea. Our data suggest that years in which these features were closer to the South Orkney shelf were also years of positive Southern Annular Mode and higher observed krill densities. Our findings highlight existing fishery?predator?prey overlap in the region and support the hypothesis that Weddell Sea oceanography may play a role in transporting krill into this region. These results will feed into the next phase of krill fisheries management assessment.
Publisher: John Wiley & Sons, Ltd
Keywords: Scotiahavet; Sør-Orknøyene; Sørishavet; Weddellhavet; ekkolodd; fiskerier; krill; oseanografi; plankton

Inferring the seasonality of sea ice floes in the Weddell Sea using ICESat-2 - Gupta, M.; Regan, H.; Koo, Y.; Chua, S. M. T.; Li, X.; Heil, P. (The Cryosphere, 2025)
Over the last decade, the Southern Ocean has experienced episodes of severe sea ice area decline. Abrupt events of sea ice loss are challenging to predict, in part due to incomplete understanding of processes occurring at the scale of individual ice floes. Here, we use high-resolution altimetry (ICESat-2) to quantify the seasonal life cycle of floes in the perennial sea ice pack of the Weddell Sea. The evolution of the floe chord distribution (FCD) shows an increase in the proportion of smaller floes between November and February, which coincides with the asymmetric melt–freeze cycle of the pack. The freeboard ice thickness distribution (fITD) suggests mirrored seasonality between the western and southern sections of the Weddell Sea ice cover, with an increasing proportion of thicker floes between October and March in the south and the opposite in the west. Throughout the seasonal cycle, there is a positive correlation between the mean chord length of floes and their average freeboard thickness. Composited floe profiles reveal that smaller floes are more vertically round than larger floes and that the mean roundness of floes increases during the melt season. These results show that regional differences in ice concentration and type at larger scales occur in conjunction with different behaviors at the small scale. We therefore suggest that floe-derived metrics obtained from altimetry could provide useful diagnostics for floe-aware models and improve our understanding of sea ice processes across scales.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; fjernmåling; havis; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article Number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; klimaendringer; marin biologi; marin økologi

Sex Differentiation and Long-Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Schiavon, Luca; Desvignes, Thomas; Ronco, Fabrizia; Matschiner, Michael; Gastaldi, Martina; Koppetsch, Thore; Schrøder-Nielsen, Audun; Postlethwait, John H.; Prestanti, Alessia; Stranci, Federica; Ceballos, Santiago G.; Mark, Felix C.; et al. (Ecology and Evolution, 2025)
Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD-seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.
Publisher: John Wiley & Sons, Ltd Article number: e71847
Keywords: Sørishavet; Weddellhavet; biodiversitet; fiskerier; genetikk; marin biologi; marin økologi

Observations of the Antarctic Slope Current in the Southeastern Weddell Sea: A Bottom-Enhanced Current and Its Seasonal Variability - Darelius, Elin; Fer, Ilker; Janout, Markus; Daae, Kjersti; Steiger, Nadine (Journal of Geophysical Research: Oceans, 2024)
Abstract The Antarctic Slope Front and the associated Antarctic Slope Current dynamically regulate the exchanges of heat across the continental shelf break around Antarctica. Where the front is weak, relatively warm deep waters reach the ice shelf cavities, contributing to basal melting and ultimately affecting sea level rise. Here, we present new 2017?2021 records from two moorings deployed on the upper continental slope (530 and 738 m depth) just upstream of the Filchner Trough in the southeastern Weddell Sea. The structure and seasonal variability of the frontal system in this region, central to the inflow of warm water toward the large Filchner-Ronne Ice Shelf, is previously undescribed. We use the records to describe the mean state and the seasonal variability of the regional hydrography and the southern part of the Antarctic Slope Current. We find that (a) the current is, contrary to previous assumptions, bottom-enhanced, (b) the isotherms slope upwards toward the shelf break, and more so for warmer isotherms, and (c) the monthly mean thermocline depth is shallowest in February-March and deepest in May-June while (d) the current is strongest in April-June. On monthly timescales, we show that (e) positive temperature anomalies of the de-seasoned records are associated with weaker-than-average currents. We propose that the upward-sloping isotherms are linked to the local topography and conservation of potential vorticity. Our results contribute to the understanding of how warm ocean waters propagate southward and potentially affect basal melt rates at the Filchner-Ronne Ice Shelf.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020666
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi

Stepwise Oligocene–Miocene breakdown of subpolar gyres and strengthening of the Antarctic Circumpolar Current - Hoem, F. S.; van den Broek, K.; López-Quirós, A.; van de Lagemaat, S. H. A.; Bohaty, S. M.; Hillenbrand, C.-D.; Larter, R. D.; van Peer, T. E.; Brinkhuis, H.; Sangiorgi, F.; Bijl, P. K. (J. Micropalaeontol., 2024)
Through the Cenozoic (66–0 Ma), the dominant mode of ocean surface circulation in the Southern Ocean transitioned from two large subpolar gyres to circumpolar circulation with a strong Antarctic Circumpolar Current (ACC) and complex ocean frontal system. Recent investigations in the southern Indian and Pacific oceans show warm Oligocene surface water conditions with weak frontal systems that started to strengthen and migrate northwards during the late Oligocene. However, due to the paucity of sedimentary records and regional challenges with traditional proxy methods, questions remain about the southern Atlantic oceanographic transition from gyral to circumpolar circulation, with associated development of frontal systems and sea ice cover in the Weddell Sea. Our ability to reconstruct past Southern Ocean surface circulation and the dynamic latitudinal positions of the frontal systems has improved over the past decade. Specifically, increased understanding of the modern ecologic affinity of organic-walled dinoflagellate cyst (dinocyst) assemblages from the Southern Ocean has improved reconstructions of distinct past oceanographic conditions (sea surface temperature, salinity, nutrients, and sea ice) using downcore assemblages from marine sediment records. Here we present new late Oligocene to latest Miocene (∼ 26–5 Ma) dinocyst assemblage data from marine sediment cores in the southwestern Atlantic Ocean (International Ocean Discovery Program (IODP) Site U1536, Ocean Drilling Program (ODP) Site 696 and piston cores from Maurice Ewing Bank). We compare these to previously published latest Eocene–latest Miocene (∼ 37–5 Ma) dinocyst assemblage records and sea surface temperature (SST) reconstructions available from the SW Atlantic Ocean in order to reveal oceanographic changes as the Southern Ocean gateways widen and deepen. The observed dinocyst assemblage changes across the latitudes suggest a progressive retraction of the subpolar gyre and southward migration of the subtropical gyre in the Oligocene–early Miocene, with strengthening of frontal systems and progressive cooling since the middle Miocene (∼ 14 Ma). Our data are in line with the timing of the removal of bathymetric and geographic obstructions in the Drake Passage and Tasmanian Gateway regions, which enhanced deep-water throughflow that broke down gyral circulation into the Antarctic circumpolar flow. Although the geographic and temporal coverage of the data is relatively limited, they provide a first insight into the surface oceanographic evolution of the late Cenozoic southern Atlantic Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; Sørishavsstrømmen; Weddellhavet; mikropaleontologi; oseanografi

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Observed Pathways and Interannual Variability of the Warm Inflow Onto the Continental Shelf in the Southern Weddell Sea - Steiger, N.; Sallée, J. B.; Darelius, Elin; Janout, Markus; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2024)
Model projections suggest that the continental shelf in the southern Weddell Sea may experience a shift from today's near-freezing temperature to a much warmer state, where warm water floods the shelf and basal melt rates beneath the Filchner Ronne Ice Shelf increase dramatically. Today, the Filchner Trough serves as a conduit for the southward flow of Warm Deep Water (WDW) during summer and, thus, requires continuous monitoring of its hydrographic conditions. An extensive network of moorings was installed at key sites along the inflow pathway from 2017 to 2021, to expand on existing mooring records starting in 2014. The moorings complemented with under-ice profiling floats reveal two inflow pathways, where WDW enters along the eastern flank of the Filchner Trough as well as through a smaller trough east of there. Within the observed period, 2017 and 2018 feature anomalously warm inflows. The inflow is regulated by the heaving of isopycnals over the continental slope, and the southward propagation toward Filchner Ice Shelf is two times faster during these warm years. Furthermore, the warm years coincide with low summer sea ice concentration, which enhances surface stratification through increased freshwater input and modifies sea ice-ocean stresses that both act to lift the warm water layer and increase the temperatures on the continental shelf. Finally, the recent record low sea ice conditions around the Antarctic emphasize the importance of our findings and raise concerns regarding a potentially increasing presence of WDW on the southern Weddell Sea shelf.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; havis; isshelf; oseanografi; sjøis

FRIS Revisited in 2018: On the Circulation and Water Masses at the Filchner and Ronne Ice Shelves in the Southern Weddell Sea - Janout, Markus A; Hellmer, Hartmut H; Hattermann, Tore; Huhn, Oliver; Sültenfuss, Jürgen; Østerhus, Svein; Stulic, Lukrecia; Ryan, Svenja; Schröder, Michael; Kanzow, Torsten (Journal of Geophysical Research: Oceans, 2021)
The Filchner-Ronne Ice Shelf (FRIS) is characterized by moderate basal melt rates due to the near-freezing waters that dominate the wide southern Weddell Sea continental shelf. We revisited the region in austral summer 2018 with detailed hydrographic and noble gas surveys along FRIS. The FRIS front was characterized by High Salinity Shelf Water (HSSW) in Ronne Depression, Ice Shelf Water (ISW) on its eastern flank, and an inflow of modified Warm Deep Water (mWDW) entering through Central Trough. Filchner Trough was dominated by Ronne HSSW-sourced ISW, likely forced by a recently intensified circulation beneath FRIS due to enhanced sea ice production in the Ronne polynya since 2015. Glacial meltwater fractions and tracer-based water mass dating indicate two separate ISW outflow cores, one hugging the Berkner slope after a two-year travel time, and the other located in the central Filchner Trough following a ∼six year-long transit through the FRIS cavity. Historical measurements indicate the presence of two distinct modes, in which water masses in Filchner Trough were dominated by either Ronne HSSW-derived ISW (Ronne-mode) or more locally derived Berkner-HSSW (Berkner-mode). While the dominance of these modes has alternated on interannual time scales, ocean densities in Filchner Trough have remained remarkably stable since the first surveys in 1980. Indeed, geostrophic velocities indicated outflowing ISW-cores along the trough's western flank and onto Berkner Bank, which suggests that Ronne-ISW preconditions Berkner-HSSW production. The negligible density difference between Berkner- and Ronne-mode waters indicates that each contributes cold dense shelf waters to protect FRIS against inflowing mWDW.
Keywords: Sørishavet; Weddellhavet; oseanografi; vannmasser

Evaluation of Three Numerical Weather Prediction Models for the Weddell Sea Region for the Austral Winter 2013 - Jonassen, Marius O; Nygård, Tiina; Vihma, Timo (Journal of Geophysical Research: Atmospheres, 2021)
It is widely recognized that numerical weather prediction (NWP) results for the Antarctic are relatively poor compared to the mid-latitudes. In this study, we evaluate output from three operational NWP systems: the ECMWF, Global Forecast System (GFS) and Antarctic Mesoscale Prediction System (AMPS), for the Austral winter (June-August) of 2013 for the Weddell Sea region, paying special attention to regional patterns of error statistics. This is the first evaluation of NWP systems over the Southern Ocean that also addresses the accuracy of forecasted vertical profiles. In the evaluation, we use data from land- and ship-based automatic weather stations (AWS) and radiosoundings. While the ECMWF and AMPS forecasts are on average biased cold and dry near the surface, the GFS forecasts are on average biased warm and moist. The near-surface wind speed is on average overestimated by the AMPS forecasts, whereas it is slightly underestimated by the forecasts of the other two NWP systems. Among the variables investigated, all three NWP systems forecast the near-surface specific humidity most accurately, followed by the temperature and then the wind speed. The forecast quality for the near-surface and upper-air wind speed degrades the most rapidly with increasing lead time, compared to the other variables. ECMWF is the overall best NWP system when compared against both the near-surface and upper-air observations, followed by AMPS and then GFS. The generally poorest model performance is found in locations with complex terrain along the coast of the Antarctic continent, and the best over the ocean.
Keywords: Sørishavet; Weddellhavet; geofysikk; meteorologi

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Antarctic petrels ‘on the ice rocks’: wintering strategy of an Antarctic seabird - Delord, Karine; Kato, Akiko; Tarroux, Arnaud; Orgeret, Florian; Cotté, Cedric; Ropert-Coudert, Yan; Cherel, Yves; Descamps, Sébastien (Royal Society Open Science, 2020)
There is a paucity of information on the foraging ecology, especially individual use of sea-ice features and icebergs, over the non-breeding season in many seabird species. Using geolocators and stable isotopes, we defined the movements, distribution and diet of adult Antarctic petrels Thalassoica antarctica from the largest known breeding colony, the inland Svarthamaren, Antarctica. More specifically, we examined how sea-ice concentration and free-drifting icebergs affect the distribution of Antarctic petrels. After breeding, birds moved north to the marginal ice zone (MIZ) in the Weddell sector of the Southern Ocean, following its northward extension during freeze-up in April, and they wintered there in April–August. There, the birds stayed predominantly out of the water (60–80% of the time) suggesting they use icebergs as platforms to stand on and/or to rest. Feather δ15N values encompassed one full trophic level, indicating that birds fed on various proportions of crustaceans and fish/squid, most likely Antarctic krill Euphausia superba and the myctophid fish Electrona antarctica and/or the squid Psychroteuthis glacialis. Birds showed strong affinity for the open waters of the northern boundary of the MIZ, an important iceberg transit area, which offers roosting opportunities and rich prey fields. The strong association of Antarctic petrels with sea-ice cycle and icebergs suggests the species can serve, year-round, as a sentinel of environmental changes for this remote region.
Keywords: Sørishavet; Weddellhavet; biologi; geolokalisering; havis; isberg; isfjell; klimaendringer; miljøendringer; ornitologi; petreller; sjøfugler; sjøis; økologi

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Coherent Seasonal Acceleration of the Weddell Sea Boundary Current System Driven by Upstream Winds - Le Paih, Nicolas; Hattermann, Tore; Boebel, Olaf; Kanzow, Torsten; Lüpkes, Christof; Rohardt, Gerd; Strass, Volker; Herbette, Steven (Journal of Geophysical Research: Oceans, 2020)
The Weddell Sea is of global importance in the formation of dense bottom waters associated with sea ice formation and ocean-ice sheet interaction occurring on the shelf areas. In this context, the Weddell Sea boundary current system (BCS) presents a major conduit for transporting relatively warm water to the Weddell Sea ice shelves and for exporting some modified form of Wedell Sea deep and bottom waters into the open ocean. This study investigates the downstream evolution of the structure and the seasonality of the BCS along the Weddell Sea continental slope, combining ocean data collected for the past two decades at three study locations. The interannual-mean geostrophic flow, which follows planetary potential vorticity contours, shifts from being surface intensified to bottom intensified along stream. The shift occurs due to the densification of water masses and the decreasing surface stress that occurs westward, toward the Antarctic Peninsula. A coherent along-slope seasonal acceleration of the barotropic flow exists, with maximum speed in austral autumn and minimum speed in austral summer. The barotropic flow significantly contributes to the seasonal variability in bottom velocity along the tip of the Antarctic Peninsula. Our analysis suggests that the winds on the eastern/northeastern side of the gyre determines the seasonal acceleration of the barotropic flow. In turn, they might control the export of Weddell Sea Bottom Water on seasonal time scales. The processes controlling the baroclinic seasonality of the flow need further investigation.
Keywords: Sørishavet; Weddellhavet; batymetri; havstrømmer; innlandsis; kontinentalmargin; oseanografi

Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

Ecological niche modelling of cold-water corals in the Southern Ocean (N Antarctic), present distribution and future projections due to temperature changes - Chaabani, Safa; López-González, Pablo J; Casado-Amezua, Pilar; Pehlke, Hendrik; Weber, Lukas; Martínez-Baraldés, Irene; Jerosch, Kerstin (Marine Ecology Progress Series, 2019)
An urgent necessity to understand the effect of climatic change on scleractinian cold-water coral (CWC) ecosystems has arisen due to increasing ocean warming and acidification over the last decades. Here, presence-absence records of 12 scleractinian CWC species from research expeditions and the literature were compiled and merged with model-generated pseudo-absence data and 14 environmental variables. The best-fitting results of 9 species distribution models (SDMs) were combined to an ensemble habitat suitability model for CWCs in the northern Southern Ocean (Weddell Sea and Antarctic Peninsula) by means of the open-source R package "biomod2". Furthermore, 2 future scenarios of increasing bottom sea temperature were used to investigate the spatial response of scleractinians to temperature change. The resulting (current scenario) potential ecological niches were evaluated with good to excellent statistical measures. The results predict that present areas of highest probability of CWC occurrence are around the Antarctic Peninsula, South Orkney Islands and Queen Maud Land, with preference to geomorphic features such as seamounts. The distribution of CWC habitats is mainly driven by distance to coast and ice shelves, bathymetry, benthic calcium carbonate, and temperature. Under warming conditions, CWCs are predicted to expand their distribution range by 6 and 10% in 2037 and 2150, respectively, compared to the present distribution. The future models using increased bottom temperature revealed a stable CWC distribution for most parts of the study area. However, habitat shifts are expected to the Filchner Trough region, the adjacent continental shelves, as well as to the eastern side of the Antarctic Peninsula. KEYWORDS: Scleractinian coral · Ensemble models · Environmental change · Habitat suitability model · Spatial distribution · Weddell Sea. Antarctica
Keywords: Sørishavet; Weddellhavet; batymetri; biodiversitet; global oppvarming; klimaendringer; marin biologi; miljøendringer; oseanografi; økosystemer

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Wind Stress Mediated Variability of the Filchner Trough Overflow, Weddell Sea - Daae, Kjersti Birkeland; Darelius, Elin Maria K; Fer, Ilker; Østerhus, Svein; Ryan, Svenja (Journal of Geophysical Research: Oceans, 2018)
Keywords: Sørishavet; Weddellhavet; forskning; havstrømmer; oseanografi

Seasonal Outflow of Ice Shelf Water Across the Front of the Filchner Ice Shelf, Weddell Sea, Antarctica - Darelius, Elin Maria K; Sallée, Jean-Baptiste (Geophysical Research Letters, 2018)
Keywords: Sørishavet; Weddellhavet; bunnvann; isfront; isshelf; oseanografi

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

Spring phenology shapes the spatial foraging behavior of Antarctic petrels - Fauchald, Per; Tarroux, Arnaud; Tveraa, Torkild; Cherel, Yves; Ropert-Coudert, Yan; Kato, Akiko; Love, Oliver P; Varpe, Øystein; Descamps, Sébastien (Marine Ecology Progress Series, 2017)
In polar seas, the seasonal melting of ice triggers the development of an open-waterecosystem characterized by short-lived algal blooms, the grazing and development of zooplank-ton, and the influx of avian and mammalian predators. Spatial heterogeneity in the timing of icemelt generates temporal variability in the development of these events across the habitat, offeringa natural framework to assess how foraging marine predators respond to the spring phenology.We combined 4 yr of tracking data of Antarctic petrels Thalassoica antarcticawith synopticremote-sensing data on sea ice and chlorophyll ato test how the development of melting ice andprimary production drive Antarctic petrel foraging. Cross-correlation analyses of first-passagetime revealed that Antarctic petrels utilized foraging areas with a spatial scale of 300 km. Theseareas changed position or disappeared within 10 to 30 d and showed no spatial consistency amongyears. Generalized additive model (GAM) analyses suggested that the presence of foraging areaswas related to the time since ice melt. Antarctic petrels concentrated their search effort in meltingareas and in areas that had reached an age of 50 to 60 d from the date of ice melt. We found nosignificant relationship between search effort and chlorophyll aconcentration. We suggest thatthese foraging patterns were related to the vertical distribution and profitability of the main prey,the Antarctic krill Euphausia superba. Our study demonstrates that the annual ice melt in theSouthern Ocean shapes the development of a highly patchy and elusive food web, underscoringthe importance of flexible foraging strategies among top predators. KEY WORDS: Area-restricted search · Euphausia superba· Marginal ice zone · Phytoplanktonbiomass · Procellariiformes · Sea ice dynamics · Southern Ocean · Thalassoica antarctica
Keywords: Sørishavet; Weddellhavet; biologi; biomasse; fenologi; fytoplankton; fôring; havis; klima; petreller; sjøis; smelting; økosystemer

Distribution, density and abundance of Antarctic ice seals off Queen Maud Land and the eastern Weddell Sea - Gurarie, Eliezer; Bengtson, John L; Bester, Marthán N; Blix, Arnoldus Schytte; Cameron, Michael; Bornemann, Horst; Nordøy, Erling S; Plötz, Joachim; Steinhage, Daniel; Boveng, Peter (Polar Biology, 2017)
Keywords: Sørishavet; Weddellhavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr; zoologi

Seasonal cycle of hydrography on the eastern shelf of the Filchner Trough, Weddell Sea, Antarctica - Ryan, Svenja; Hattermann, Tore; Darelius, Elin Maria K; Schröder, Michael (Journal of Geophysical Research: Oceans, 2017)
Keywords: Sørishavet; Weddellhavet; hydrografi; isshelf; kontinentalsokkel; kontinentalsokler

Observed vulnerability of Filchner-Ronne Ice Shelf to wind-driven inflow of warm deep water - Darelius, Elin Maria K; Fer, Ilker; Nicholls, Keith William (Nature Communications, 2016)
Keywords: Antarktis; Weddellhavet; isshelf; oseanografi; sjøvann

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi

Hydrography and circulation in the Filchner Depression, Weddell Sea, Antarctica - Darelius, Elin Maria K; Makinson, Keith; Daae, Kjersti Birkeland; Fer, Ilker; Holland, Paul R; Nicholls, Keith W (Journal of Geophysical Research: Oceans, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; havstrømmer; hydrografi; isfront; isshelf

On the Seasonal Signal of the Filchner Overflow, Weddell Sea, Antarctica - Darelius, Elin Maria K; Strand, Kjersti Opstad; Østerhus, Svein; Gammelsrød, Tor; Årthun, Marius; Fer, Ilker (Journal of Physical Oceanography, 2014)
Keywords: Sørishavet; Weddellhavet; bunnvann; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi; sjøvann

Atmosphere–sea ice interaction in early summer in the Antarctic: evaluation and challenges of a regional atmospheric model - Valkonen, T.; Vihma, T.; Johansson, M. M.; Launiainen, J. (Quarterly Journal of the Royal Meteorological Society, 2014)
Antarctic sea ice areas have only been the main focus for a few studies combining observations and three-dimensional atmospheric model experiments. This study presents simulations over the Weddell Sea in early summer, applying the polar-optimized version of the Weather Research and Forecasting model (Polar WRF). The results are compared against observations from the drifting experiment Ice Station Polarstern, which took place on 28 November 2004?2 January 2005. The Polar WRF model showed good skill in simulating synoptic-scale variations. The diurnal cycles of surface variables were reproduced, but the amplitude was overestimated for most of the variables and the simulations were characterized by a cold temperature bias at night. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were found to be associated with clouds, atmospheric boundary-layer processes and processes in the sea ice and snow layer. Temporal variations in the errors in cloud cover generated large errors in long-wave radiation fluxes. In the boundary layer, the overestimated downward sensible heat flux was partly compensated for by the underestimated downward long-wave radiation at the surface. The underestimated downward long-wave flux started to dominate as the stability increased and generated the cold temperature bias at the surface. Problems with the surface energy balance, as found in this study, could be reduced by applying more advanced schemes for snow and ice thermodynamics.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; meteorologi; sjøis

Wind-driven spreading of fresh surface water beneath ice shelves in the Eastern Weddell Sea - Zhou, Qiming; Hattermann, Tore; Nøst, Ole Anders; Biuw, Martin; Kovacs, Kit M; Lydersen, Christian (Journal of Geophysical Research: Oceans, 2014)
Abstract Solar heated, fresh Antarctic Surface Water (ASW) is a permanent feature along the Eastern Weddell Sea (EWS) coast in summer down to a depth of roughly 200 m. Recently, ASW has been observed beneath the Fimbul Ice Shelf, suggesting that it might play an important role in basal melting. We propose that wind-driven coastal downwelling is the main mechanism that spreads ASW beneath the ice shelf in this sector of Antarctica. We validate this hypothesis with observations, scaling analyses, and numerical modeling, along three principle lines: (i) data analyses of about 1500 salinity profiles collected by instrumented seals indicate that the observed freshening of the coastal water column is likely explained by the on-shore Ekman transport and subsequent downwelling of ASW; (ii) an analytical model of the coastal momentum balance indicates that wind-driven downwelling is capable of depressing the buoyant surface water to a depth similar to the ice shelf draft; and (iii) simulations from both idealized and regional eddy-resolving numerical ice shelf/ocean models support our proposition. Our main conclusion is that wind-driven spreading of ASW beneath the ice shelf occurs when downwelling exceeds the depth of the ice shelf base. Furthermore, our study adds to the understanding of the oceanic processes at the Antarctic Slope Front in the EWS, with possible implications for other sectors of Antarctica.
Keywords: Sørishavet; Weddellhavet; isbrem; isshelf; oseanografi; overflatevann; smelting; vannmasser; vannvirvler

Eddy-Driven Exchange between the Open Ocean and a Sub–Ice Shelf Cavity - Årthun, Marius; Holland, Paul R; Nicholls, Keith William; Feltham, Daniel L (Journal of Physical Oceanography, 2013)
Keywords: Sørishavet; Weddellhavet; isshelf; oseanografi; sjøvirvler; vannvirvler

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

Environmental conditions, particle flux and sympagic microalgal succession in spring before the sea-ice break-up in Adélie Land, East Antarctica - Riaux-Gobin, Catherine; Dieckmann, Gerhard S; Poulin, Michel; Neveux, Jacques; Labrune, Céline; Vétion, Gilles (Polar Research, 2013)
Data pertaining to environmental conditions, sympagic (sea ice) microalgal dynamics and particle flux were collected before the spring ice break-up 2001 in Pierre Lejay Bay, adjacent to the Dumont d'Urville Station, Petrel Island, East Antarctica. An array of two multiple sediment traps and a current meter was deployed for five weeks, from 8 November to 6 December 2001. The sea-ice chlorophyll a and particulate organic carbon (POC) averaged 0.6 mg l−1 (30 mg m−2) and 20 mg l−1 (1 g m−2) near the coast. The POC export flux that reached a maximum of 79 mg m−2 d−1 during the study period was high compared to the one for the Weddell Sea. The flux was homogeneous from the surface to 47 m depth and increased sharply 33 days before the effective ice break-up. A north-western progressive vector of currents (i.e., Lagrangian drift) in the sub-ice surface waters was demonstrated. Bottom ice, platelet ice and under-ice water at 5 m were characterized by differences in colonization and short-term succession of microalgae. Keywords: Land-fast ice; oceanic short-term regime; POM flux; sympagic communities; East Antarctica.
Keywords: Sørishavet; Weddellhavet; alger; fysisk oseanografi; geokjemi; havis; sjøis; sympagisk økologi

Circulation and exchanges at high-latitude ocean margins : dynamical models and observations from instrumented seals - Zhou, Qin; Eltoft, Torbjørn (UiT The Arctic University of Norway, 2013)
Circulation and exchange processes at high-latitude ocean margins are investigated in this thesis, by using analytical models, numerical simulations and hydrographic data. In the Northern Hemisphere, the establishment of Atlantic Water transport as a topographically steered slope current has been investigated. A simplified analytical model based on geostrophic balance predicts that buoyancy loss over a sloping boundary leads to a cross-slope baroclinic flow transformed into an along-slope barotropic flow. And the resulting transport changes can be estimated from hydrographic data. Over the continental slope off Scotland, the diagnosed transport changes in the barotropic flow is in agreement with the observed transport changes. The results emphasize that geostrophy can be used to diagnose topographically steered barotropic flow, which makes it especially useful for high latitudes where topographic steering of ocean circulation is strong. In the Eastern Weddell Sea in the Atlantic Sector of Antarctica, the processes controlling the exchanges of water masses over the continental slope have been studied, by taking advantage of over 11,000 hydrographic profiles collected by instrumented seals in this region from February to November 2008. The proposed mechanism, that the wind-driven downwelling is responsible for the accumulation of Antarctic Surface Water near the ice front and its further spreading beneath the ice shelf along the coast of Eastern Weddell Sea, is revisited by a combination of detailed analysis of the data collected by the seals, an analytical model and numerical simulations. The results show that the Antarctic Surface Water enters the ice shelf cavity after being brought on-shore by wind-driven surface Ekman transport, and being spread below the depth of the ice base within a regime of coastal downwelling. The results also suggest a complex picture of water mass exchange processes along the coast of Eastern Weddell Sea, in which mesoscale eddies play a central role. Finally, the data collected by the seals are employed to evaluate the performance of a global coupled ocean-ice model incorporated with a parametrization of wave-induced mixing in simulating the upper ocean properties in the Southern Ocean. The results suggest that wave-induced mixing is important to modify the upper ocean properties. Since coastal water properties in the Eastern Weddell Sea are mainly determined by the onshore Ekman transport of surface waters, the wave-induced mixing also plays a role in preconditioning the coastal water masses in this region. I dette arbeidet er sirkulasjon og blandingsmekanismer i havområder på høge breddegrader undersøkt ved bruk av analytiske modeller, numeriske simuleringer og havobservasjoner. På den nordlige halvkulen er det undersøkt hvordan transport av Atlanterhavsvann etablerer seg som en topografisk styrt strøm langs kontinentalsokkelskråningen. En forenklet analytisk modell basert på geostrofisk balanse kan forklare hvordan varmetap i vannet som strømmer langs en skrånende bunn fører til en baroklin strøm på tvers av skråningen som igjen blir transformert til en barotrop strøm langs den skrånende bunnen. Denne transportendringen kan man beregne fra hydrografiske data. En slik beregnet transportendring over kontinentalsokkelskråningen vest for Skotland stemmer godt overens med observert transportendring i denne regionen. Resultatene understreker at geostrofi kan bli brukt til å diagnostisere topografisk styrte strømmer, noe som gjør teorien spesielt egnet for å studere oseanografi på høge breddegrader der topografisk styring av strømmene er mest tydelig. I det østlige Weddellhavet, i den atlantiske sektoren av Antarktis, har prosessene som styrer vannmasseutvekslingen på tvers av kontinentalsokkelskråningen blitt undersøkt ved å ta i bruk mer enn 11.000 havprofiler som er blitt samlet inn av seler i denne regionen fra februar til november 2008. Selene var utsyrt med temperatur-, salt- og dybde-loggere. Den foreslåtte mekanismen at vind-drevet nedstrømning er ansvarlig for oppsamling av antarktisk overflatevann nær isbremmen og for dens videre spredning under den flytende isbremmen langs kysten av den østlige Weddellhavet, er testet ved hjelp av en kombinasjon av detaljerte dataanalyser av observasjonene som ble samlet inn av selene, en analytisk modell og numeriske simuleringer. Resultatene viser at det antarktiske overflatevannet entrer hulområdet under isbremmen etter at det er blitt fraktet mot isbremmen som Ekman-transport i overflaten. Spredningen på undersiden av den flytende isbremmen kan forklares ved hjelp av samme mekanisme som nedstrømning langs en kyst. Resultatene tyder også på at vannmasseutvekslingen langs kysten av det østlige Weddellhavet er sammensatt av flere prosesser der virvler av mesoskala størrelse spiller en sentral rolle. Til slutt er dataene som ble samlet inn av selene blitt brukt til å evaluere en global hav-is-modell som har innebygget en parameterisering av bølgedrevet blanding i Sørhavet. Resultatene indikerer at bølgedrevet blanding er viktig for å modifisere hva de øvre vannmassene i Sørhavet er sammensatt av. Siden sammensetningen i kystvann i det østlige Weddellhavet er hovedsakelig bestemt av Ekmantransport inn mot kysten, vil bølgedrevet blanding også spille en rolle når det gjelder å danne kystvannmassene i denne regionen.
Publication Title: Universitetet i Tromsø, Fakultet for naturvitenskap og teknologi Volume: Ph.D. Issue: DOKTOR-004
Keywords: Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Seasonal inflow of warm water onto the southern Weddell Sea continental shelf, Antarctica - Årthun, Marius; Nicholls, Keith William; Makinson, Keith; Fedak, Michael A; Boehme, Lars (Geophysical Research Letters, 2012)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; oseanografi

Southern Weddell Sea shelf edge geomorphology: Implications for gully formation by the overflow of high-salinity water - Gales, Jennifer A; Larter, Robert David; Mitchell, Neil; Hillenbrand, Claus-Dieter; Østerhus, Svein; Shoosmith, Deb R (Journal of Geophysical Research: Earth Surface, 2012)
Keywords: Sørishavet; Weddellhavet; forskning; geomorfologi; isshelf; oseanografi

Ice Shelf - Ocean Interaction in the Eastern Weddell Sea, Antarctica - Hattermann, Tore (Universitetet i Tromsø, 2012)
This thesis investigates the interaction of the Antarctic ice shelves along the coast of Dronning Maud Land with the ocean circulation in the Eastern Weddell Sea. A set of direct oceanic observations below the Fimbul Ice Shelf, which were acquired during three Antarctic field seasons in the austral summers 2009/10, 2010/11 and 2011/12, is a central element of the presented work. This new oceanographic dataset is complemented by a high-resolution state-of-the-art ice shelf - ocean circulation model. The results provide an estimate of the amount of basal melting at the Fimbul Ice Shelf, and revise the physical processes that determine the ocean heat fluxes over the East Antarctic continental slope. A major finding is that deep-ocean heat fluxes towards the ice are much more constrained than predicted by previous ocean models, causing substantially lower rates of basal melting than earlier suggested. The predicted basal melting is consistent with mass balance estimates from satellite data and implicates that the Fimbul Ice Shelf is currently not subject to rapid basal mass loss. Furthermore, the complex interplay of the processes within the coastal, frontal system, and their respective role in transporting heat for melting towards the ice is examined. The results emphasize the importance of oceanic eddies within the coastal circulation for controlling the inflow of Warm Deep Water into the ice shelf cavities. A realistic representation of the effect of the mesoscale eddy overturning is thus a crucial requirement in order to simulate basal melting along the Weddell Sea coast in the present and future climate. The results also imply that fresh, and solar-heated Antarctic Surface Water plays a central role for the ice shelf cavity exchange. Being produced by sea ice melting at the ocean surface, this water mass directly enters the cavity and increases the melting of shallow ice. Due to its buoyancy, the presence of Antarctic Surface Water also alters the coastal dynamics and regulates the inflow of warm water at depth, thus showing that a more detailed understanding of the role of this water mass for basal melting around Antarctica will need further attention. Finally, the results suggest a direct relationship between the simulated basal melting and only a few deterministic parameters of the coastal circulation, which is used to derive a simple parameterization of for basal melting at the Fimbul Ice Shelf.
Publication Title: Faculty of science and technology. Department of physics and technology Volume: Philosophiae Doctor Issue: DOKTOR-004 ISBN: 8282360783,9788282360784,8282360791,9788282360791
Keywords: Sørishavet; Weddellhavet; fysikk; fysisk oseanografi; isbrem; isshelf; klimaendringer

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Low-ozone events in the southern polar summer as indicated by Met Office ozone analyses - Jackson, David; Orsolini, Yvan Joseph; Engelsen, Ola (Journal of Geophysical Research: Atmospheres, 2011)
Southern summer low-ozone events (LOEs) are examined using Met Office ozone analyses for 2005–2007. At 31 hPa, tongues of low-ozone air are pulled out of the polar region and extend to lower latitudes. Low tongues are also seen at 100 hPa, but there the low ozone is transported from low to high latitudes. These low tongues are frequently superimposed on one another, meaning that there are often also reductions in total ozone. What is striking is that at high latitudes, summer total ozone is typically lower over the Weddell Sea than at other longitudes. The low-ozone tongues at 31 and 100 hPa are consistent with transport associated with planetary waves. Daily geopotential height fields show a poleward and westward wave tilt with height, indicating the presence of baroclinic waves. The tilt enables the superimposition of the low-ozone tongues at 100 and 31 hPa. Filtered geopotential height anomalies reveal the presence of waves reported in other studies and indicate the connection between tropospheric and stratospheric wave dynamics in driving the LOEs. There is also a high connection between the LOEs and ultraviolet (UV) Index. The Weddell Sea region gets up to 20–30% more UV than the zonal mean, and the tip of South America gets about 10–25% more. There have been numerous studies of the impacts of increased UV on the Antarctic marine ecosystem during the springtime ozone hole, and our results indicate there is a case for these studies being extended to the summer LOEs.
Keywords: Antarktis; UV-stråling; Weddellhavet; ozonlaget; polarområdene; stratosfæren; ultrafiolett stråling

Eddy overturning of the Antarctic Slope Front controls glacial melting in the Eastern Weddell Sea - Nøst, Ole Anders; Biuw, Martin; Tverberg, Vigdis; Lydersen, Christian; Hattermann, Tore; Zhou, Qianhe; Smedsrud, Lars Henrik; Kovacs, Kit M (Journal of Geophysical Research: Oceans, 2011)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; oseanografi

Using fluorescence to characterize dissolved organic matter in Antarctic sea ice brines - Stedmon, Colin A; Thomas, David N; Papadimitriou, Stathys; Granskog, Mats A; Dieckmann, Gerhard S (Journal of Geophysical Research: Biogeosciences, 2011)
Sea ice plays a dynamic role in the air-sea exchange of CO2. In addition to abiotic inorganic carbon fluxes, an active microbial community produces and remineralizes organic carbon, which can accumulate in sea ice brines as dissolved organic matter (DOM). In this study, the characteristics of DOM fluorescence in Antarctic sea ice brines from the western Weddell Sea were investigated. Two humic-like components were identified, which were identical to those previously found to accumulate in the deep ocean and represent refractory material. Three amino-acid-like signals were found, one of which was unique to the brines and another that was spectrally very similar to tryptophan and found both in seawater and in brine samples. The tryptophan-like fluorescence in the brines exhibited intensities higher than could be explained by conservative behavior during the freezing of seawater. Its fluorescence was correlated with the accumulation of nitrogen-rich DOM to concentrations up to 900 μmol L−1 as dissolved organic carbon (DOC) and, thus, potentially represented proteins released by ice organisms. A second, nitrogen-poor DOM fraction also accumulated in the brines to concentrations up to 200 μmol L−1 but was not correlated with any of the fluorescence signals identified. Because of the high C:N ratio and lack of fluorescence, this material is thought to represent extracellular polymeric substances, which consist primarily of polysaccharides. The clear grouping of the DOM pool into either proteinaceous or carbohydrate-dominated material indicates that the production and accumulation of these two subpools of DOM in sea ice brines is, to some extent, decoupled.
Keywords: Sørishavet; Weddellhavet; fluorescens; gassutveksling; havis; karbondioksid; marin økologi; mikrobielle organismer; mikrobiologi; sjøis

Observations of the Antarctic Slope Undercurrent in the southeastern Weddell Sea - Chavanne, Cédric P; Heywood, Karen J; Nicholls, Keith W; Fer, Ilker (Geophysical Research Letters, 2010)
The Antarctic Slope Front presents a dynamical barrier between the cold Antarctic shelf waters in contact with ice shelves and the warmer subsurface waters offshore. Two hydrographic sections with full-depth current measurements were undertaken in January and February 2009 across the slope and shelf in the southeastern Weddell Sea. Southwestward surface-intensified currents of ∼30 cm s−1, and northeastward undercurrents of 6–9 cm s−1, were in thermal-wind balance with the sloping isopycnals across the front, which migrated offshore by 30 km in the time interval between the two sections. A mid-depth undercurrent on February 23 was associated with a 130-m uplift of the main pycnocline, bringing Warm Deep Water closer to the shelf break. This vertical displacement, comparable to that caused by seasonal variations in wind speed, implies that undercurrents may affect the exchanges between coastal and deep waters near the Antarctic continental margins.
Keywords: Sørishavet; Weddellhavet; hydrografi; isbrem; isshelf; kontinentalmargin; kontinentalsokkel; oseanografi; understrømmer

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Data-based estimation of anthropogenic carbon and acidification in the Weddell Sea on a decadal timescale - Hauck, J.; Hoppema, M.; Bellerby, R. G. J.; Völker, C.; Wolf-Gladrow, D. (Journal of Geophysical Research: Oceans, 2010)
The amount of anthropogenic CO2 (Cant) that entered the Weddell Sea between 1992 and 2008 (Cant1992?2008) was assessed using the extended multiple linear regression (eMLR) method. In the Warm Deep Water (WDW) and the Weddell Sea Bottom Water (WSBW), Cant1992?2008 values were insignificant, whereas values as high as 8 ?mol kg?1 were observed over the shelf. Cant1992?2008 concentrations in the surface layer varied with latitude between 2 and 11 ?mol kg?1. Weak intrusion of anthropogenic CO2 into Weddell Sea Deep Water (WSDW) was demonstrated (Cant1992?2008 yields 1.5?2 ?mol kg?1). That more Cant1992?2008 was found in the WSDW than in the WSBW is surprising, but can be explained by intense ventilation of the WSDW originating from east of the Weddell Gyre. The invasion of Cant1992?2008 provokes a shift in the equilibria of the carbonate system, resulting in acidification and reduction of CO32? concentration. The mean decrease of pH in the upper 200 m layer was 0.016. The largest decrease of calcite and aragonite saturation states was observed at the surface. This implies that surface waters might become undersaturated with respect to aragonite in the future while the underlying WDW is still saturated. Results of this analysis suggest that complete undersaturation of surface waters in the Weddell Sea will be reached after the 21st century.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; havforsuring; karbondioksid; oseanografi

Wintertime mixed layer measurements at Maud Rise, Weddell Sea - Sirevaag, Anders; McPhee, Miles G; Morison, James H; Shaw, William J; Stanton, Timothy P (Journal of Geophysical Research: Oceans, 2010)
Sea ice plays a crucial role in the exchange of heat between the ocean and the atmosphere, and areas of intense air-sea-ice interaction are important sites for water mass modification. The Weddell Sea is one of these sites where a relatively thin first-year ice cover is constantly being changed by mixing of heat from below and stress exerted from the rapidly changing and intense winds. This study presents mixed layer turbulence measurements obtained during two wintertime drift stations in August 2005 in the eastern Weddell Sea, close to the Maud Rise seamount. Turbulence in the boundary layer is found to be controlled by the drifting ice. Directly measured heat fluxes compare well with previous studies and are well estimated from the mixed layer temperatures and mixing. Heat fluxes are also found to roughly balance the conductive heat flux in the ice; hence, little freezing/melting was observed. The under-ice topography is estimated to be hydraulically very smooth; comparison with a steady 1-D model shows that these estimates are made too close to the ice-ocean interface to be representative for the entire ice floe. The main source and sink of turbulent kinetic energy are shear production and dissipation. Observations indicate that the dynamics of the under-ice boundary layer are influenced by a horizontal variability in mixed layer density and an increasing amount of open leads in the area.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; havis; hydrografi; oseanografi; pyknoklin; sjøis

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Satellite microwave observations of the interannual variability of snowmelt on sea ice in the Southern Ocean - Willmes, Sascha; Haas, Christian; Nicolaus, Marcel; Bareiss, Jörg (Journal of Geophysical Research: Oceans, 2009)
Snowmelt processes on Antarctic sea ice are examined. We present a simple snowmelt indicator based on diurnal brightness temperature variations from microwave satellite data. The method is validated through extensive field data from the western Weddell Sea and lends itself to the investigation of interannual and spatial variations of the typical snowmelt on Antarctic sea ice. We use in-situ measurements of physical snow properties to show that despite the absence of strong melting, the summer period is distinct from all other seasons with enhanced diurnal variations of snow wetness. A microwave emission model reveals that repeated thawing and refreezing cause the typical microwave emissivity signatures that are found on perennial Antarctic sea ice during summer. The proposed melt indicator accounts for the characteristic phenomenological stages of snowmelt in the Southern Ocean and detects the onset of diurnal snow wetting. An algorithm is presented to map large-scale snowmelt onset based on satellite data from the period between 1988 and 2006. The results indicate strong meridional gradients of snowmelt onset with the Weddell, Amundsen, and Ross Seas showing earliest (beginning of October) and most frequent snowmelt. Moreover, a distinct interannual variability of melt onset dates and large areas of first-year ice where no diurnal freeze thawing occurs at the surface are determined.
Article Number: C03006
Keywords: Amundsenhavet; Rosshavet; Sørishavet; Weddellhavet; fjernmåling; havis; miljøsatellitter; oseanografi; sjøis; snøsmelting

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Halo of ice deformation observed over the Maud Rise seamount - Lindsay, Ronald; Kwok, Ronald; de Steur, Laura; Meier, Walt (Geophysical Research Letters, 2008)
A distinctive halo of sea ice deformation was observed above the Maud Rise seamount in the eastern Weddell Sea in the winter of 2005. The deformation halo is coincident with a halo of low mean ice concentration that is often observed in the region. Monthly mean ice vorticity estimates for the months July through November reveal the deformation zone most clearly in an arc about 100 km northwest of the seamount where there is a strong gradient in the bathymetry at depths of 3000–5000 m. The deformation was computed from satellite-based ice motion vectors derived from Envisat Synthetic Aperture Radar backscatter images. The deformation halo is evidence of a Taylor cap circulation over the seamount, which has been described and analyzed with modeling studies and concurrent oceanographic observations obtained during an extensive field campaign.
Keywords: Sørishavet; Weddellhavet; havis; havstrømmer; hydrografi; oseanografi; sjøis; vannvirvler

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

Effect of critical latitude and seasonal stratification on tidal current profiles along Ronne Ice Front, Antarctica - Makinson, Keith; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2006)
Keywords: Antarktis; Weddellhavet; havstrømmer; isfront; isshelf; oseanografi; tidevannsstrømmer

Modeling ocean processes below Fimbulisen, Antarctica - Smedsrud, Lars H.; Jenkins, Adrian; Holland, David M.; Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2006)
Model simulations of circulation and melting beneath Fimbulisen, Antarctica, obtained using an isopycnic coordinate ocean model, are presented. Model results compare well with available observations of currents and hydrography in the open ocean to the north of Fimbulisen and suggest that Warm Deep Water exists above the level of a sub-ice-shelf bedrock sill, the principal pathway for warm waters to enter the sub-ice-shelf cavity. The model shows a southward inflow of Warm Deep Water over this sill and into the cavity, producing a mean cavity temperature close to −1.0°C. This leads to high levels of basal melting (>10 m/a) at the grounding line of Jutulstraumen and an average melting over the ice shelf base close to 1.9 m/a. The southward inflow is a compensating flow caused by the northward outflow of fresh, cold water produced by the basal melting. Results on inflow and melting are difficult to validate since no in situ measurements yet exist in the cavity. If such high melt rates are realistic, the mass balance of Fimbulisen must be significantly negative, and the ice shelves along Dronning Maud Land must contribute about 4.4 mSv of melt water to the Weddell Sea, about 15% of the total Antarctic meltwater input to the Southern Ocean.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; geofysikk; hydrografi; isshelf; oseanografi

Southern Ocean deep-sea isopod species richness (Crustacea, Malacostraca): influences of depth, latitude and longitude - Brandt, Angelika; Ellingsen, Kari E.; Brix, Saskia; Brökeland, Wiebke; Malyutina, Marina (Polar Biology, 2005)
We examined deep-sea epibenthic sledge isopod data from the Atlantic sector of the Southern Ocean (SO) (depth range=742–5,191 m). Samples were taken during the expeditions EASIZ II (ANT XV-3) in 1998 and ANDEEP I and II (ANT XIX3/4) in 2002. A total of 471 isopod species were recorded from 28 sites. The species richness of the epibenthic sledge samples was highly variable (6–82 species). Species richness was highest at site 131-3 in 3,053 m depth in the north-eastern Weddell Sea. The highest numbers of species were sampled in the middle depth range and lower species richness was found in the shallower and deeper parts of the study area. Depth is suggested to explain isopod species richness better than both latitude and longitude. Between 58°S and 65°S, the number of species ranged from 9 to 82 (mean=35.9). Further south in the Weddell Sea, between 73°S and 74°S, species richness was lower and the number of species ranged from 6 to 35 (mean=19.2). With regard to longitude, the highest species richness (up to 82 species) was found between 50°W and 60°W in the area of the South Shetland Islands and around the Antarctic Peninsula, while numbers did not exceed 50 species in the eastern Weddell Sea. The haul length, ranging from 807 to 6,464 m, was positively correlated with depth; however, there was no linear relationship between haul length and species richness. We therefore suggest that depth was the most important factor explaining isopod species richness. However, only 28 sites were visited and the statistical power is thus limited. Sampling in the deep sea is expensive and time consuming and as yet this is the best isopod data set available from the Atlantic sector of the SO. Future expeditions are therefore important to better explain the current patterns of benthic diversity in Antarctica.
Keywords: Sør-Shetlandsøyene; Sørishavet; Weddellhavet; biodiversitet; isopoder; marin biologi

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Publisher: Microbiology Society Type: Journal Article
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Warming of the deep water in the Weddell Sea along the Greenwich meridian: 1977–2001 - Smedsrud, Lars H. (Deep Sea Research Part I: Oceanographic Research Papers, 2005)
The Weddell Deep Water (WDW) warmed substantially along the Greenwich meridian following the Weddell Polynya of the 1970s. Areas affected by the polynya contained ∼14GJ/m2 more heat in 2001 than in 1977. This warming would require a flux of ∼390W/m2 if it were to take place over a year. Large variations in heat content of the WDW are found between the Antarctic coast and Maud Rise (64°S). The small variation found north of Maud Rise is opposite in phase to that to the south, and the warming was close to monotonic south of 68°S. The mean warming of WDW along the section is ∼0.032°C per decade, comparable to the warming of the Antarctic Circumpolar Current. The mean warming compares with a surface heat flux of 4W/m2 over the 25 year period, an order of magnitude higher than the warming of the global ocean. As variation in mean salinity of the WDW follows the warming/cooling events, variation in inflow probably explains a cooling event between 1984 and 1989, and a warming event between 1989 and 1992. Cooling during the late 1990s is probably related to the reappearance of a polynya like feature in some winter months as an area 100km in diameter close to Maud Rise with 10–20% lower sea ice concentrations than the surrounding ocean.
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi; polynja

Isolation and partial characterization of a parapoxvirus isolated from a skin lesion of a Weddell seal - Tryland, M.; Klein, J.; Nordøy, E.S.; Blix, A.S. (Virus Research, 2005)
A solitary skin lesion was found on the neck of a Weddell seal (Leptonychotes weddellii), chemically immobilized in Queen Maud Land (70°09′S, 05°22′E) Antarctica 2001. The lesion was elevated and 3cm in diameter, consisting of partly fresh and partly necrotic tissue, and proliferative papilloma-like structures were seen. Electron microscopy on a biopsy from the lesion revealed typical parapoxvirus particles. Polymerase chain reaction (PCR; B2L gene) generated amplicons of approximately 594 base pairs, comparable to Orf-virus, the prototype parapoxvirus. A comparison of these B2L PCR amplicon DNA sequences with corresponding sequences from other parapoxviruses, showed that the Weddell seal virus resembled isolates from grey seal (Halichoerus grypus) and harbour seal (Phoca vitulina) more than parapoxvirus from red deer (Cervus elaphus), sheep, cattle and Japanese serows (Capricornis crispus). It is thus concluded that the Weddell seal parapoxvirus belong to the tentative seal parapoxvirus species. Since parapox and orthopoxviruses may cause similar clinical diseases, we suggest that the term sealpox should be restricted to the clinical disease, whereas seal parapoxvirus should be used when caused by a parapoxvirus, rather than the general term “sealpox virus”. This is the first verified case of parapoxvirus infection in a Weddell seal, and also the first report of any such infections in the Antarctic.
Keywords: Dronning Maud Land; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi; pinnipedier; seler; virologi

Interannual controls on Weddell Sea surface water fCO2 during the autumn–winter transition phase - Bellerby, Richard G.J.; Hoppema, Mario; Fahrbach, Eberhard; de Baar, Hein J.W.; Stoll, Michel H.C. (Deep Sea Research Part I: Oceanographic Research Papers, 2004)
The fugacity of carbon dioxide (fCO2) of the surface waters of the Weddell Sea along the prime meridian has been described for the austral autumn in 1996 and 1998. For individual years, fCO2 has a strong linear relationship with sea surface temperature, although the relationships cannot be reconciled to provide an interannually consistent algorithm for remotely sensed assessment of fCO2. However, from the assumption that Weddell Sea surface water has a single end member (upwelled Warm Deep Water) we have determined the relative contributions of heating, ice-melt, and biological activity on fCO2. A breakdown of the controls shows that the measured annual fCO2 distributions can be recreated for both transects by adjusting solely for thermodynamic forcing, and model adjustments for salinity are small except in regions of significant upwelling during 1998. The incorporation of nitrate utilisation into the model results in a general and significant underestimation of fCO2. This runs contrary to the earlier findings of Sabine and Key (Mar. Chem. 60 (1998) 95) in the Southern Ocean although it is consistent with models in the area (Louanchi et al., Deep-Sea Res. I 48 (2001) 1581). A major caveat to these findings is the significant departure of the thermodynamic model and a tightening of the nitrate-adjusted model in 1998 in areas with deeper mixing in the southern Weddell Sea. We propose that there are two reasons for the discrepancies in our model: the source waters are not as homogenous as the model assumes; and there are geographical and seasonal variations of CO2 exchange with the atmosphere and the input of inorganic carbon and nitrate from below the mixed layer resulting in imbalances in the mixed layer concentration ratios.
Keywords: Sørishavet; Weddellhavet; karbon syklus; karbondioksid; marin biologi; marin kjemi; oseanografi

A survey of amphipod associates of sea urchins, with description of new species in the genera Lepidepecreella (Lysianassoidea: lepidepecreellid group) and Notopoma (Photoidea: Ischyroceridae) from Antarctic cidarids - Berge, Jørgen; Vader, Wim; Lockhart, Susanne (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
The known associations between amphipods and echinoids are listed, separated into five different categories depending upon the nature of the associations. The new species Lepidepecreella andeep, found attached around the mouth of the cidarid sea urchin Aporocidaris antarctica, is described, as well as the new species Notopoma cidaridis. The tubes of the latter were found attached to the spines of the cidarid sea urchin Rhynchocidaris triplopora. These cases represent the first associations reported between amphipods and echinoids in the Antarctic. A key to both genera is provided.
Keywords: Sørishavet; Weddellhavet; amfipoder; krepsdyr; pigghuder; sjøpiggsvin; taksonomi; zoologi

Ice shelf water overflow and bottom water formation in the southern Weddell Sea - Foldvik, Arne; Gammelsrød, Tor; Østerhus, Svein; Fahrbach, Eberhard; Rohardt, Gerd; Schröder, Michael; Nicholls, Keith William; Padman, Laurie; Woodgate, Rebecca A. (Journal of Geophysical Research: Oceans, 2004)
Cold shelf waters flowing out of the Filchner Depression in the southern Weddell Sea make a significant contribution to the production of Weddell Sea Bottom Water (WSBW), a precursor to Antarctic Bottom Water (AABW). We use all available current meter records from the region to calculate the flux of cold water (<−1.9°C) over the sill at the northern end of the Filchner Depression (1.6 ± 0.5 Sv), and to determine its fate. The estimated fluxes and mixing rates imply a rate of WSBW formation (referenced to −0.8°C) of 4.3 ± 1.4 Sv. We identify three pathways for the cold shelf waters to enter the deep Weddell Sea circulation. One path involves flow constrained to follow the shelf break. The other two paths are down the continental slope, resulting from the cold dense water being steered northward by prominent ridges that cross the continental slope near 36°W and 37°W. Mooring data indicate that the deep plumes can retain their core characteristics to depths greater than 2000 m. Probably aided by thermobaricity, the plume water at this depth can flow at a speed approaching 1 m s−1, implying that the flow is occasionally supercritical. We postulate that such supercriticality acts to limit mixing between the plume and its environment. The transition from supercritical to slower, more uniform flow is associated with very efficient mixing, probably as a result of hydraulic jumps.
Keywords: Sørishavet; Weddellhavet; havstrømmer; isshelf; oseanografi

Seasonal ventilation of the cavity beneath Filchner-Ronne Ice Shelf simulated with an isopycnic coordinate ocean model - Jenkins, Adrian; Holland, David M.; Nicholls, Keith W.; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
The ocean cavity beneath Filchner-Ronne Ice Shelf is observed to respond to the seasonal cycle of water mass production on the continental shelf of the southern Weddell Sea. Here we use a numerical model to investigate the propagation of newly formed shelf waters into the cavity. We find that the model reproduces the most distinctive features of the observed seasonality and offers a plausible explanation for those features. The most saline shelf waters are produced in the far west, where the inflow to the cavity peaks twice each year. The major peak occurs during the short period around midwinter when convection reaches full depth and the densest waters are generated. Once the surface density starts to decline, dynamic adjustment of the restratified water column leads to a gradual fall in the salinity at depth and a secondary peak in the inflow that occurs in summer at the western coast. Beneath the ice shelf the arrival of the wintertime inflow at the instrumented sites is accompanied by a rapid warming, while the slower decline in the inflow leads to a more gradual cooling. Water brought in by the secondary, summer peak flows mainly to the eastern parts of the cavity. Here the seasonality is suppressed because the new inflows mix with older waters that recirculate within a topographic depression. This pooling of waters in the east, where the primary outflow of Ice Shelf Water is generated, dampens the impact of seasonality on the local production of Weddell Sea Bottom Water.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Interannual variability and ventilation timescales in the ocean cavity beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
Multiyear time series of ocean current and temperatures from beneath Filchner-Ronne Ice Shelf, Antarctica, demonstrate both seasonal and interannual variability. The seasonal signal is visible at all measurement sites, although it was swamped for a 2-year period (1999–2001) when extraordinarily light sea-ice cover in the southern Weddell Sea during the 1997–1998 Austral summer caused an anomalously large pulse of High Salinity Shelf Water to flush beneath the ice shelf. The pulse was observed twice at an instrumented site near the Berkner Island coast, once on its way to the Filchner Depression and once after the signal had propagated around the depression and returned to the site as an anomalously large pulse of Ice Shelf Water. The timings of the signal allow an estimate of 24–30 months for the flushing timescales of the sub-ice shelf ocean cavity, indicating that the cavity is highly responsive to external forcing. A timescale for the full ventilation of the cavity of 4–5 years is obtained from the length of time the sub-ice shelf conditions take to return to their original state, a timescale significantly shorter than previous estimates.
Keywords: Antarktis; Weddellhavet; geofysikk; havstrømmer; oseanografi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Decadal decrease of Antarctic sea ice extent inferred from whaling records revisited on the basis of historical and modern sea ice records - Ackley, Stephen; Wadhams, Peter; Comiso, Josefino C; Worby, Anthony P (Polar Research, 2003)
In previous work, whaling catch positions were used as a proxy record for the position of the Antarctic sea ice edge and mean sea ice extent greater than the present one spanning 2.8° latitude was postulated to have occurred in the pre-1950s period, compared to extents observed since 1973 from microwave satellite imagery. The previous conclusion of an extended northern latitude for ice extent in the earlier epoch applied only to the January (mid-summer) period. For this summer period, however, there are also possible differences between ship and satellite-derived measurements. Our work showed a consistent summer offset (November– December), with the ship-observed ice edge 1 - 1.5° north of the satellitederived ice edge. We further reexamine the use of whale catch as an ice edge proxy where agreement was claimed between the satellite ice edge (1973–1987) and the ship whale catch positions. This examination shows that, while there may be a linear correlation between ice edge position and whale catch data, the slope of the line deviates from unity and the ice edge is also further north in the whale catch data than in the satellite data for most latitudes. We compare the historical (direct) record and modern satellite maps of ice edge position accounting for these differences in ship and satellite observations. This comparison shows that only regional perturbations took place earlier, without significant deviations in the mean ice extents, from the pre-1950s to the post-1970s. This conclusion contradicts that previously stated from the analysis of whale catch data that indicated Antarctic sea ice extent changes were circumpolar rather than regional in nature between the two periods.
Keywords: Sørishavet; Weddellhavet; endringer; havis; historisk; hvalfangere; hvalfangst; iskant; observasjoner; satellite bilder; sjøis

A 1.3-Myr palaeoceanographic record from the continental margin off Dronning Maud Land, Antarctica - Forsberg, Carl Fredrik; Løvlie, Reidar; Jansen, Eystein; Solheim, Anders; Sejrup, Hans Petter; Lie, Hans Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A 12.5 m long core was retrieved from the continental margin off Dronning Maud Land, Antarctica. Magnetostratigraphy, stable isotopes, 14C accelerator mass spectrometer and amino acid analyses indicate a continuous sediment record going back 1.3 Myr. Comparison of CaCO3 results with those from ODP Site 1089 and an index of North Atlantic Deep Water (NADW) influence in surface waters indicate that NADW upwelled along the Antarctic continental margin during the whole of this period. The mid-Pleistocene transition (1.0–0.6 Ma) was accompanied by an apparent decline in the NADW influence, and was followed by extended carbonate dissolution during the interglacials of marine isotope stages (MIS) 13 and 11. Less extensive periods of dissolution occur at the end of the interglacials younger than MIS 11. While interglacial dissolution is characteristic of the Pacific and Indian oceans, the carbon isotopes return to pre-transition values indicative of renewed NADW upwelling. The concentration of ice-rafted debris may reflect changes in the relative rate of interglacial sedimentation. It is speculated that the high ice rafted debris (IRD) concentrations during interglacials younger than 400 kyr may be due to a reduced relative sedimentation rate of other interglacial components whereas the low concentrations during interglacials before the mid-Pleistocene transition may be due to a higher relative sedimentation rate of these.
Keywords: Dronning Maud Land; Weddellhavet; geologi; magnetostratigrafi; oseanografi; paleoklimatologi; paleoseanografi; stabile isotoper

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

Water mass modification over the continental shelf north of Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Padman, Laurie; Schröder, Michael; Woodgate, Rebecca A.; Jenkins, Adrian; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2003)
We use new data from the southern Weddell Sea continental shelf to describe water mass conversion processes in a formation region for cold and dense precursors of Antarctic Bottom Water. The cruises took place in early 1995, 1998, and 1999, and the time series obtained from moored instruments were up to 30 months in length, starting in 1995. We obtained new bathymetric data that greatly improve our definition of the Ronne Depression, which is now shown to be limited to the southwestern continental shelf and so cannot act as a conduit to northward flow from Ronne Ice Front. Large-scale intrusions of Modified Warm Deep Water (MWDW) onto the continental shelf occur along much of the shelf break, although there is only one location where the MWDW extends as far south as Ronne Ice Front. High-Salinity Shelf Water (HSSW) produced during the winter months dominates the continental shelf in the west. During summer, Ice Shelf Water (ISW) exits the subice cavity on the eastern side of the Ronne Depression, flows northwest along the ice front, and reenters the cavity at the ice front's western limit. During winter the ISW is not observed in the Ronne Depression north of the ice front. The flow of HSSW into the subice cavity via the Ronne Depression is estimated to be 0.9 ± 0.3 Sv. When combined with inflows along the remainder of Ronne Ice Front (reported elsewhere), sufficient heat is transported beneath the ice shelf to power an average basal melt rate of 0.34 ± 0.1 m yr−1.
Art. no. 3260
Keywords: AABW; Sørishavet; Weddellhavet; geofysikk; havstrømmer; isshelf; kontinentalsokkel; oseanografi

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Low phytoplankton biomass and ice algal blooms in the Weddell Sea during the ice-filled summer of 1997 - Hegseth, Else Nøst; Quillfeldt von, Cecilie Hellum (Antarctic Science, 2002)
The summer of 1997 was characterized by unusually large amounts of pack ice in the southeastern Weddell Sea, and less than 10% of the area that is commonly ice-free in summer was open. A modest phytoplankton bloom developed in the upper mixed layer in the northernmost area (72°S). The bloom peaked in mid-February with max chlorophyll concentrations of 1.5 μg l−1, and integrated stocks of 55–60 mg m−2. Autotrophic flagellates dominated the biomass (80–90% of the chlorophyll) at first, while diatoms increased relative to flagellates during the bloom. Nutrient deficits, however, indicated that a much larger biomass was produced than was observed. Freezing starting after mid-February probably terminated the bloom, resulting in a pelagic growth season limited in time (less than two months) and space. The sea ice had a distinct brown layer of algae, usually at 1–2 m depth, with average chlorophyll biomass of 10.3 mg m−2. The ice cover exhibited a substantial amount of ridges, with ice algae growing in cavities and other structures, but with lower biomass than in the bands. Ice algae were also found growing on the lower 2 m of the ice shelf (visible at low tide). The overall growth season in the ice lasted several months, and ice algal production may have exceeded pelagic production in the Weddell Sea during the growth season of 1997. Pennate diatoms, like Fragilariopsis curta and F. cylindrus, dominated both in ice and in open water above the pycnocline, while Phaeocystis antarctica dominated in deeper layers and in crack pools. Euphausiids, particularly young stages, were frequently observed grazing on ice algae in ridges and on all sides of the floes, (confirmed by the gut content). Ice algae would thus have served as an ample food supply for the krill in the summer of 1997.
Edition: 2004/04/22 Publisher: Cambridge University Press
Keywords: Sørishavet; Weddellhavet; fytoplankton; havis alger; hydrografi; krill; oseanografi

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

Oceanographic measurements near Fimbulisen ice shelf - O'Dwyer, Jane; Nøst, Ole Anders; Karlsen, Tor Ivan; Søreide, Janne; Jensen, Glen; Fransson, Agneta; Savinov, Vladimir (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; Weddellhavet; glasiologi; hydrografi; oseanografi

Current measurements near Ronne Ice Shelf: implications for circulation and melting - Foldvik, Arne; Gammelsrød, Tor; Nygaard, E.; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2001)
We present the first year-long current meter records ever obtained near the floating Filchner-Ronne Ice Shelf in the Weddell Sea. The currents are steered along the ice front, but in the lower layer where the bottom topography is descending toward the west the current has a component toward the ice front of about 3 cm s−1. During winter the temperature stayed near the surface freezing point, while the salinity increased, indicating that ice was formed and brine released. The seasonal variation in salinity was 0.15±0.05 psu, corresponding to the formation of 1–2 m of ice on a shelf depth of 400 m. The transport of High-Salinity Shelf Water (HSSW) into the ice shelf cavity was found to be of the order 0.5×106 m3 s−1. The production of this water due to oscillating tides and off shelf winds was found to be of the same order of magnitude. In contact with glacial ice at great depths, and because of the depression of the freezing point, the HSSW is transformed to Ice Shelf Water (ISW) by cooling and melting processes. The melting rate was estimated to 1×1011 ton yr−1. This corresponds to the melting of 0.2 m ice per year if the melting is evenly distributed over the Filchner-Ronne Ice Shelf. If the melting is concentrated along a path from the Berkner Shelf around the Berkner Island to the Filchner Depression, then melting rates up to 7 m yr−1 must be expected. A comparison of HSSW characteristics in the Ronne Depression, our winter observations on the Berkner Shelf, and the ISW flowing out of the Filchner Depression indicates that very little water passes through the cavity from the Ronne to the Filchner Depression. It appears that most of the ISW originating from processes on the Berkner Shelf escapes the cavity in the Filchner Depression. This leaves the Berkner Shelf as the important source of ISW and subsequently of the Weddell Sea Bottom Water formed from ISW.
Keywords: Antarktis; Weddellhavet; havstrømmer; isshelf; oseanografi

Direct measurements reveal insignificant storage of anthropogenic CO2 in the Abyssal Weddell Sea - Hoppema, Mario; Roether, Wolfgang; Bellerby, Richard G. J.; de Baar, Hein J. W. (Geophysical Research Letters, 2001)
In the northern Weddell Gyre at the prime meridian, Total TCO2 changes in the Weddell Sea Bottom Water (WSBW) have been investigated. Following a suggestion by [Poisson and Chen, 1987], the TCO2 difference at potential temperatures of 0.2°C and −0.8°C was determined using data from 1996 and 1998. No significant difference was found to similar differences for the years 1973 and 1981 reported by Poisson and Chen. Thus, over a period of 25 years an at most minor amount of anthropogenic CO2 has penetrated into the WSBW at this location. This suggests that this abyssal subpolar region is relatively unimportant for the storage of anthropogenic CO2. The same core of WSBW exhibited a marked increase of chlorofluorocarbon (CFC). For the Southern Ocean, therefore, CFCs are apparently of limited value as analogues of anthropogenic CO2, in contrast to some other ocean provinces.
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; drivhusgasser; geofysikk; klimagasser

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Shelf progradation on a glaciated continental margin, Queen Maud Land, Antarctica - Kristoffersen, Yngve; Winterhalter, Boris; Solheim, Anders (Marine Geology, 2000)
A detailed survey of the continental margin in the eastern Weddell Sea demonstrates shelf progradation by material input from discrete glacial wedges that amalgamate to form the present near rectilinear shelf edge. Kvitkuven Ice Rise is located between two trough mouth fans and rests on a thick sediment substratum that predates the shelf sequences north of it. Shelf progradation, west of the ice rise, preceded the progradation east of it. In this way the seaward progression of a shelf edge may reflect the broad scale expansion of the East Antarctic Ice Sheet, but the timing of shelf progradation can be different in adjacent areas. The progradational glacial wedges on the continental shelf mapped by this survey are correlated stratigraphically to be within the post Late Miocene glacial sequence, drilled at ODP Site 693 on the middle continental slope 200 km to the northeast. Two submarine moraine ridge complexes on the shelf parallel the shelf edge. A radiocarbon age of 18:950 280 years BP from the front of the inner complex (water depth 319 m) suggests that grounded ice at most reached the present mid-shelf area in front of the ice rise during the Late Wisconsin Glacial Maximum, or had retreated to this position at that time.
Keywords: Dronning Maud Land; Weddellhavet; marin geofysikk; marin geologi; oseanografi; seismisk stratigrafi